Clinical COPD Questionnaire in patients with chronic respiratory disease. Issue 7 (14th August 2014) - Canavan, Jane L.; Dilaver, Deniz; Clark, Amy L.; Jones, Sarah E.; Nolan, Claire M.; Kon, Samantha S. C.; Man, William D.‐C.
Abstract Background and objective The Clinical Chronic Obstructive Pulmonary Disease (COPD) Questionnaire (CCQ) is an easy to complete, health‐related quality of life questionnaire which has been well‐validated in COPD. The responsiveness of the CCQ in chronic respiratory disease patients other than COPD has not been previously described. The study aims were to determine if the CCQ in chronic respiratory disease correlates with other health related quality of life questionnaires, to assess the responsiveness of the CCQ to pulmonary rehabilitation and to determine the minimum important difference. Methods The CCQ, COPD Assessment Test (CAT), the Chronic Respiratory Questionnaire (CRQ) and St George's Respiratory Questionnaire (SGRQ) were measured in 138 chronic respiratory disease patients completing pulmonary rehabilitation. Change in CCQ with pulmonary rehabilitation was correlated with change in the other questionnaires. The minimum important difference of the CCQ was calculated using distribution and anchor‐based approaches. Results The CCQ, CAT, CRQ and SGRQ improved significantly with rehabilitation with effect sizes of −0.43, −0.26, 0.62, −0.37. Change in CCQ correlated significantly with CAT, CRQ and SGRQ (r = 0.53, −0.64, 0.30, all P < 0.0001). The minimum important difference was −0.42 at the population level and −0.4 at the individual level. Conclusions The CCQ is responsive to pulmonary rehabilitation in chronic respiratory disease patients, with an MID estimated at −0.4 at the individual level.